2021
DOI: 10.3390/biom11050679
|View full text |Cite
|
Sign up to set email alerts
|

In Search of a Role for Extracellular Purine Enzymes in Bone Function

Abstract: Bone is one of the major tissues that undergoes continuous remodeling throughout life, thus ensuring both organic body growth during development and protection of internal organs as well as repair of trauma during adulthood. Many endogenous substances contribute to bone homeostasis, including purines. Their role has increasingly emerged in recent decades as compounds which, by interacting with specific receptors, can help determine adequate responses of bone cells to physiological or pathological stimuli. Equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…To date, only a few reports have interrogated the role of purine metabolism on bone. 56 Elevated adenosine was shown to increase osteoclastogenesis while ADA that catalyses the conversion of adenosine to inosine significantly suppressed osteoclast differentiation. 57 Likewise, we used ADA inhibitors in our study to block adenosine metabolisation into inosine/hypoxanthine on L-arginine treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few reports have interrogated the role of purine metabolism on bone. 56 Elevated adenosine was shown to increase osteoclastogenesis while ADA that catalyses the conversion of adenosine to inosine significantly suppressed osteoclast differentiation. 57 Likewise, we used ADA inhibitors in our study to block adenosine metabolisation into inosine/hypoxanthine on L-arginine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, we observed that L-arginine altered purine metabolism, substantially increasing inosine and hypoxanthine and decreasing adenosine after TNFα stimulation. To date, only a few reports have interrogated the role of purine metabolism on bone 56. Elevated adenosine was shown to increase osteoclastogenesis while ADA that catalyses the conversion of adenosine to inosine significantly suppressed osteoclast differentiation 57.…”
Section: Discussionmentioning
confidence: 99%
“…In birds, uric acid, a purine compound, serves as the end product of nitrogen catabolism originating from the microbes, is rapidly cleared from the blood by the kidneys. Purines have been shown to be involved in continuous bone remodeling by bone cells, allowing the skeleton to grow and repair itself, which is achieved in a balance of osteoclasts and osteoblasts, eventually purine metabolism likely contributing to dynamic bone homeostasis ( Schwartz, 1978 ; Stentoft et al, 2015 ; Zuccarini et al, 2021 ). Studies on the vitamin metabolism affecting bone growth and development mainly focused on vitamin D, which is associated with osteoporosis ( Binkley, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, BMSCs can differentiate into osteoblasts and adipoblasts, and purinergic receptors all of which are involved in the dynamic regulation of this process (Jorgensen,2019;Zuccarini et al,2021). Purinergic receptors are cell membrane receptors that can speci cally bind to adenosine or purine nucleotides.…”
mentioning
confidence: 99%
“…The P2 receptor family is divided into two subtypes: P2X (1-7), which are ligand-gated ion channel, and P2Y (1, 2, 4, 6, 11, 12, 13, and 14), which are G-protein-coupled receptors [14]. Extracellular nucleotides are released into the cell matrix as soluble factors and exert signals through speci c P2 receptors on the cell surface in an autocrine or paracrine manner [12]. After activation of P2 receptors, phospholipase C (PLC)/Ca 2+ and other related signal pathways are triggered which regulate a variety of processes involved in bone metabolism, where P2Y6 plays an important role in osteogenesis [15,16].…”
mentioning
confidence: 99%